2009
DOI: 10.1074/jbc.m109.005611
|View full text |Cite
|
Sign up to set email alerts
|

C1q Tumor Necrosis Factor α-related Protein Isoform 5 Is Increased in Mitochondrial DNA-depleted Myocytes and Activates AMP-activated Protein Kinase

Abstract: Depletion of mtDNA in myocytes causes insulin resistance and alters nuclear gene expression that may be involved in rescuing processes against cellular stress. Here we show that the expression of C1q tumor necrosis factor ␣-related protein isoform 5 (C1QTNF5) is drastically increased following depletion of mtDNA in myocytes. C1QTNF5 is homologous to adiponectin in respect to domain structure, and its expression and secretion from myocytes correlated negatively with the cellular mtDNA content. Similar to adipon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
108
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 30 publications
4
108
2
Order By: Relevance
“…We designated this novel cDNA and its encoded protein CTRP15/myonectin. While current work was ongoing, Lim et al (31) reported on a distantly related but distinct C1q family member, CTRP5 (C1qTNF5), in human and had inadvertently coined the term myonectin for CTRP5, although that term was not used in a previous CTRP5 study by the same authors (32). Given that mouse myonectin cDNA and protein sequences (HQ285249 and ADP00570, respectively) were deposited in the GenBank database and released to the public prior to the study by Lim et al (31), we propose that CTRP5 retains its original designation (20,33) and CTRP15 retains its current designation as myonectin to prevent confusion in nomenclature.…”
Section: Resultsmentioning
confidence: 99%
“…We designated this novel cDNA and its encoded protein CTRP15/myonectin. While current work was ongoing, Lim et al (31) reported on a distantly related but distinct C1q family member, CTRP5 (C1qTNF5), in human and had inadvertently coined the term myonectin for CTRP5, although that term was not used in a previous CTRP5 study by the same authors (32). Given that mouse myonectin cDNA and protein sequences (HQ285249 and ADP00570, respectively) were deposited in the GenBank database and released to the public prior to the study by Lim et al (31), we propose that CTRP5 retains its original designation (20,33) and CTRP15 retains its current designation as myonectin to prevent confusion in nomenclature.…”
Section: Resultsmentioning
confidence: 99%
“…Besides CTRP13, recent studies show that CTRP5 and CTRP6 can also activate the AMPK signaling pathway to promote glucose uptake and fatty acid oxidation (18,19). Although bacterially produced recombinant GST-CTRP5 fusion protein can activate the AMPK signaling pathway in mouse myotubes (18), its prominent expression in the eye suggests a primary role in the visual system (14,45).…”
Section: Discussionmentioning
confidence: 99%
“…Although bacterially produced recombinant GST-CTRP5 fusion protein can activate the AMPK signaling pathway in mouse myotubes (18), its prominent expression in the eye suggests a primary role in the visual system (14,45). Indeed, mutation in the CTRP5 gene has been found to cause late onset macular degeneration in humans (45,71).…”
Section: Discussionmentioning
confidence: 99%
“…14 CTRP5 has been shown to promote AMPK signaling in cultured myotubes, thereby leading to increased glucose uptake. 15 CTRP13 has also been shown to stimulate glucose uptake in adipocytes, myotubes, and hepatocytes in vitro through its ability to promote AMPK signaling, suggesting a role in glucose metabolism. 16 Furthermore, transgenic overexpression of CTRP1 will activate AMPK signaling in skeletal muscle and ameliorate metabolic dysfunction under conditions of overnutrition.…”
Section: Article See P 3159mentioning
confidence: 99%